1, 8‐cineole and castor oil in sodium lauryl ether sulphate disrupt reproduction and ovarian tissue of Rhipicephalus (Boophilus) microplus. Issue 3 (6th April 2020) - de Queiroz, V. T.; Campos, N. C.; Nunes, E. T.; Costa, A. V.; Coelho, J. D.; Trivilin, L. O.; de Melo, D. C. A.; Morais, P. A. B.; Martins, I. V. F.
Abstract: Essential and fixed oils have been researched as alternatives to chemical acaricides. The activity of volatile compounds from essential oils (1, 8‐cineole, citral and eugenol) at 1.0% (w/v) and fixed oil (castor oil) at 0.3% (w/v) dissolved in 2.0% (v/v) dimethyl sulfoxide (DMSO) + 0.2% (w/v) Tween 80 ® was assessed against Rhipicephalus microplus using immersion tests. 1, 8‐cineole (29.0%) and castor oil (30.2%) had the highest reproductive inhibition rate. A second experiment was performed to verify the effect of the 1, 8‐cineole (10.0% w/v) and, or castor oil (0.3% w/v) on tick reproduction using different solubilizing agents. The highest reproductive inhibition was observed for the combination of 1, 8‐cineole/castor oil (94.1%) and 1, 8‐cineole in 2.0% (w/v) sodium lauryl ether sulphate (SLES) (92.8%). A third experiment showed morphological changes in R. microplus oocytes at different stages of development, as well as in pedicel cells. The most intense effects were observed when ticks were immersed in the formulation containing 1, 8‐cineole (10.0% w/v) and castor oil (0.3% w/v) dissolved in 2% (w/v) SLES. These findings highlight the potential of this formulation as an alternative for managing cattle ticks as their cytotoxic effects can reduce R. microplus reproductive success. Abstract : 1, 8‐cineole and, or castor oil in different solubilizing agents were evaluated against Rhipicephalus microplus . Sodium lauryl ether sulphate (anionic surfactant) increased tick reproductive control with 1, 8‐cineole and, or castor oil. Cattle tick oocyte development was affected by 1, 8‐cineole and, or castor oil in sodium lauryl ether sulphate.